Proteomic profiling reveals the role of green tea polyphenols–iron oxide–chitosan nanoparticles in colorectal cancer therapy via MAPK/metabolic pathway modulation - Mohammad Fadzil, Mohammad Adi; Shafie, Nurul Husna; Ishak, Amirah Haziyah; Al-Awawdeh, Safaa; Mohd Nawi, Mohd Naeem; Abd Rashed, Aswir (Oxford University Press, 2025)
This research aimed to study the protein profiles of rat-induced colon carcinogenesis supplemented with green tea extract and iron oxide–chitosan green tea polyphenol nanoparticles. Fifteen male Sprague–Dawley rats were divided into five groups. Colon carcinogenesis was induced with azoxymethane, followed by treatments with 5-fluorouracil, green tea polyphenol extracts, or iron oxide–chitosan–encapsulated tea polyphenol nanoparticles. Liver proteomes were analysed using mass spectrometry, which revealed 2,258 proteins across all groups. Proteomic analysis revealed 20 differentially expressed proteins following the treatment with tea extracts or tea nanoparticles. These proteins were associated with pathways in cancer progression. Notably, six proteins were uniquely expressed in the nanoparticle group, including phosphatidylethanolamine-binding protein 1, which is linked to anticancer potential through modulation of the mitogen-activated protein kinase signalling pathway. These findings suggest that nanoparticles may enhance the therapeutic effects of tea polyphenols against colorectal cancer by more effectively modulating signalling pathways, oxidative stress, and energy metabolism.